Sítios gráficos e apropriação de espaços: um estudo de caso do complexo rupestre Rio do Peixe, região de Coronel João Sá, nordeste da Bahia - Lima Filho, Sebastião Lacerda de (2017)
This research studies ten archaeological sites, being nine of them of graphic records (eight painting sites and one of engraving) and one of lytic material (fixed bases of pestle and surface fragments), associated with the previous ones and closely connected to Rio do Peixe, whichcrosses the whole unit of study. Due to the intimate connection of the sites with the direct area across the river, it was considered viable to define the site as Archaeological Complex of Rio do Peixe. The sites studied are located in a geomorphological formation of the Inserberg type, characterized and described as a Monadnocks formation, which presents a residual form and varied features such as ridges and slopes,creating a flattening top surface that stands out in the landscape. The study area is located in the rural area of Coronel João Sá City, Northeast of Bahia. It stands out due to its relationship and environmental location: micro and macro scales; in the search for elements that allow to construct and to insert the graphic registers in temporal and spatial scale for the archaeological reality. The choice of this area as a work proposal was conditioned by the total absence of systematic studies on this material and its environmental dynamics. The need to identify cultural elements and their relation with the group(s) fixed in place in past periods has led us to elaborate this study and the propositions derived therefrom. This work consists, above all, of a documentation of traces exposed to a diversity of degrading factors which are subject to gradual and linear disappearance. The research problem is built on the assumption that the choice of places for fixation, graphic practice, reappropriation or use forpassage areas is not something done by chance, quite the contrary, they are detailed choices, inspected areas because they present the possibility of group interaction, and also because they show conditions so that the choices and the culture can be developed or expanded in a constant dynamic with the environment and with the most varied and diverse ecological contexts. This leads us to think about the choice of these landmarks in the landscape. We emphasize as general objective of research to reach data that contribute to the identification of the identity of pre-colonial groups that inhabited the northeast region of Bahia. The hypothesis proposes that the rock paintings of Rio do Peixe Complex, located in the high, middle and low slope, belongs to the Tradition of São Francisco. This is due to the geographic proximity where the characteristic elements have already been defined, because of the type of pigmentation used, the of cognosity pattern or the mental map of clothing, the type of themes found, the emblematic graphics of the tradition, and the type of features and supports chosen for general graphic practice. It is also suggested that the whole region, composed not only of the geomorphological complex mentioned above, may have been used as a zone of passage for different groups and for significant periods of time and that they may be attested by the material evidences, identified in the direct area of the sites and surroundings. Therefore, all intentional cultural variety or not, as well as the natural and landscape elements, gain relevance and base the reflections coming from the analyzes.